Psychometric Properties of Flourishing Scales From a Comprehensive Well-Being Assessment - Weziak-Bialowolska, Dorota; Bialowolski, Piotr; Lee, Matthew T.; Chen, Ying; VanderWeele, Tyler J.; McNeely, Eileen (Frontiers in Psychology, 2021)
In the article we develop a measure of complete well-being. The framework is derived from the theoretical model of human flourishing understood as a state in which all aspects of a human life are favorable. The approach extends beyond psychological well-being and reflects the World Health Organization definition of health that considers not only the health of body and mind but also embraces the wholeness of a person. The Well-Being Assessment (WBA) is a six-domain comprehensive instrument designed to assess holistic well-being in six domains: emotional health, physical health, meaning and purpose, character strengths, social connectedness, and financial security. Although each of these domains is distinct, all of them are nearly universally desired and all but financial security constitute ends in themselves. Data were collected from a representative sample of working adults. 276 employees participated in the pilot, 2,370 participated in the first wave and 1,209 in the second wave of the survey. The WBA showed a good-fitting (40-item, 6-factor), satisfactory reliability, test–retest correlation, convergent/discriminant validity in relation to stability over time and relevant psychological measures, as well as a good fit to the data that was invariant over time, gender, and age, education and marital status. The instrument can be of use for scientists and practitioners, clinicians, public health officials, and patients. Adoption of more holistic measures of well-being that go beyond psychological well-being may help to shift the focus from health deficiencies to health and well-being promotion.